Bradykinin Type-2 Receptor Expression Correlates with Age and Is Subjected to Transcriptional Regulation - Inka Liesmaa; Naotaka Shiota; Jorma O. Kokkonen; Petri T. Kovanen; Ken A. Lindstedt (International Journal of Vascular Medicine)
Accumulating work in experimental animals suggests that bradykinin (BK) exerts cardioprotective effects via bradykinin type-2 receptors (BK-2Rs). In human end-stage heart failure, BK-2Rs are significantly downregulated by mechanisms that have remained elusive. Heart tissues from idiopathic dilated cardiomyopathy (IDC; 𝑛=7), coronary heart disease (CHD; 𝑛=6), and normal patients (𝑛=6) were analyzed by RT-PCR, SSCP, and Western blotting. In normal and IDC hearts, BK-2R expression increased with age, with a lower relative increase in IDC hearts. BK-2R mRNA and protein levels showed a positive linear correlation, suggesting transcriptional regulation. Two known BK-2R promoter polymorphisms, −58T/C and −9/+9, were found to be present in the study population. The allelic frequencies for the C-allele in −58T/C were 0.58 in normal and CHD hearts and 0.81 in IDC hearts. Furthermore, the allelic frequencies for the −9 and +9 alleles were 0.42 and 0.58 in normal hearts and 0.64 and 0.36 in IDC hearts, respectively. All analyzed CHD hearts were homozygous for the −9 allele. Thus, the expression of cardioprotective BK-2Rs in human hearts is increased with age in normal and IDC hearts and may be regulated on the transcriptional level. Moreover, comparison of normal subjects and patients with failing hearts revealed different allelic frequencies in each of two known BK-2R gene polymorphisms.